E-Cigarette- and Vaping-Related Lung Injury (EVALI) at a Regional Hospital System in South Carolina. (18th May 2020) - Temas, Daniel; Meyer, Armin
Abstract : We report on four cases of severe lung injury and respiratory failure attributed to E-cigarette use that presented between July and August, 2019. The patients described were relatively healthy without clinically significant history of lung disease. Each developed severe acute respiratory distress shortly following E-cigarette use. In each case, the patients initially presented with considerable hypoxia and infectious-appearing pattern with elevated inflammatory markers on laboratory values. Imaging studies demonstrated a consistent pattern of widespread bilateral interstitial infiltrates with a medial distribution. All but one of the cases involved the admitted use of THC oil in E-cigarettes. There was rapid progression of illness requiring increased supplemental oxygen and in two cases, requiring urgent intubation and mechanical ventilation. No infectious organism was isolated in any case, and patients improved rapidly with the initiation of steroids. These are among the first cases reported in South Carolina and are consistent with similar cases that have been reported around the country.